Designing a Doctoral Program for Online Students - Zaitun, A.B; Siow, Heng Loke (2010)
As the global economy grew more and more competitive, the demand for higher education increases proportionately. The availability of diverse field of studies to cater for each sector’s manpower requirements led to the increase in the number of students pursuing higher education at the graduate level. The advent of Internet Technologies and improved accessibility has contributed largely towards the acceptance of e-learning. However, learning and teaching via online mode has its own challenges and rewards. This is especially so for programs that is very subjective such as the online doctoral program. There are obstacles faced by the students, supervisors, the university system and the examiners which can be addressed if the system of doctoral supervision is well formulated. Universities which are well established find it difficult to adjust to the requirements of online doctoral students’ supervision. The younger universities are adjusting their system and policies to meet new challenges. In this paper, we present to the readers our effort in designing an online doctoral program for Information and Communications and Technology (ICT). The structure of the new program is to ensure that the students will graduate on time and produce quality theses overcoming existing constraints that hinder students from obtaining a doctoral degree. The paper starts with an introduction of our university and its doctoral programs. This is followed by a description of the problems faced by students in existing doctoral systems. Next, the paper studies the doctoral programs or models adopted by three different Universities. We then present the program that we have formulated for our university. It is hoped that by sharing our work, other universities could learn from our experience and emulate our efforts. Key Words: online doctoral program, Supervision, e-learning